Successful management of infusion reaction accompanying the start of cetuximab therapy - Melichar, Bohuslav; Cerman, Jaroslav; Malírová, Eva (Supportive care in cancer, 2007)
INTRODUCTION: Cetuximab is a chimeric antibody registered for the therapy of advanced colorectal carcinoma after failure of standard chemotherapy. Rare infusion reactions that resulted in the cessation of therapy have been described after cetuximab administration. CASE DESCRIPTION: We have observed severe infusion reactions accompanied by a loss of consciousness in two patients. The patients were transferred to intensive care unit, and the treatment was continued after administration of corticosteroids under careful monitoring of vital signs without any further serious reactions. In both cases, benefit of therapy with cetuximab could be demonstrated. CONCLUSION: This experience indicates that cetuximab can be continued in patients who experience infusion reactions. Surveillance in the intensive care unit is mandatory during readministration of the drug.
Keywords: Adenocarcinoma; nádory jater; dexamethason; Humans; cetuximab; lidé středního věku; Glucocorticoids; nádory sigmoidea; Antibodies, Monoclonal; Aged; Drug Hypersensitivity; Antineoplastic Agents; Cetuximab; senioři; lidé; humanizované monoklonální protilátky; Liver Neoplasms; Sigmoid Neoplasms; Neoplasm Metastasis; Antibodies, Monoclonal, Humanized; metastázy nádorů; léková alergie; Male; Middle Aged; Dexamethasone; glukokortikoidy; monoklonální protilátky; protinádorové látky; infuzní pumpy; adenokarcinom; Infusion Pumps; mužské pohlaví